2014
DOI: 10.1177/0885066614554192
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Management of Common Gallstone-Related Emergencies

Abstract: Gallstone-related disease is among the most common clinical problems encountered worldwide. The manifestations of cholelithiasis vary greatly, ranging from mild biliary colic to life-threatening gallstone pancreatitis and cholangitis. The vast majority of gallstone-related diseases encountered in an acute setting can be categorized as biliary colic, cholecystitis, choledocholithiasis, and pancreatitis, although these diagnoses can overlap. The management of these diseases is uniquely multidisciplinary, involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 86 publications
0
14
0
4
Order By: Relevance
“…Results of majority of the studies conducted in different populations of the world in establishing role of sub hepatic drain in laparoscopic cholecystectomy patients revealed that it is associated with significant postoperative pain, increases discomfort as well as hospital stay for the patients 16,17,18. Laparoscopic cholecystectomy is primarily aimed at reducing patient’s pain, hospital stay and allows the patient a smooth and quick recovery from the operation 19,20.…”
Section: Discussionmentioning
confidence: 99%
“…Results of majority of the studies conducted in different populations of the world in establishing role of sub hepatic drain in laparoscopic cholecystectomy patients revealed that it is associated with significant postoperative pain, increases discomfort as well as hospital stay for the patients 16,17,18. Laparoscopic cholecystectomy is primarily aimed at reducing patient’s pain, hospital stay and allows the patient a smooth and quick recovery from the operation 19,20.…”
Section: Discussionmentioning
confidence: 99%
“…Right upper quadrant ultrasound has >95% sensitivity and specificity to detect gallbladder stone. 9 However, its sensitivity and specificity for diagnosing acute cholecystitis was relatively low. In the study by Borzellino et al, distention of the gallbladder, wall edema, and pericholecystitis fluid collection were used as the criteria for the presence of acute calculous cholecystitis.…”
Section: Discussionmentioning
confidence: 99%
“…Third, there might exist false negative patients in the present study. In general, CT scan is inferior to ultrasonography in detecting gallstones [ 22 ]. Therefore, gallstones are might to be missed at the institution in which CT scan is a major follow-up modality rather than ultrasonography.…”
Section: Discussionmentioning
confidence: 99%